Great War in Transcaucasia: From Ottoman Occupation to the Treaty of Kars - Vagnini, Alessandro (Mediterranean Journal of Social Sciences, 2012)
In October 1914 the Ottoman Empire declared war on the Entente joining the Central Powers. Now the Turksthreatened Russia’s Caucasian provinces and the communications within the British Empire via the Suez Canal but the maincampaign of the Ottoman army would extend from southern Caucasus to eastern Asia Minor. Between 1914 and 1917 thesituation on this front was quite difficult for the Turks, only the collapse of the Russian forces would change this situation. InNovember 1917, a first government of an independent Transcaucasia was created in Tbilisi while the Ottomans aiming atcreating their own rule on southern Caucasus launched a new offensive toward Baku. The Russian Revolution and thecapitulation of the Central Powers, however, open the way to the rivalry between Caucasian nationalities which will be solvedonly with the arrival of the Soviet forces. Notwithstanding, the conflict between Armenians and Azerbaijani can not find adefinitive solution even if the Treaty of Kars restored at list a stable border between Kemalist Turkey and Bolshevik Russia.